Causes of Internet Addiction in the Context of Individual Involvement in Professional Activity - Ghazaryan, Lusine (Bulletin of Yerevan University E: Philosophy, Psychology, 2024)
The relevance of the article's topic is due to the fact that in the 21st century, the internet has experienced rapid development as a means for individuals to engage in professional activities, obtain information, communicate virtually, and meet various social needs. In this context, the information society is facing a socio-psychological phenomenon that has been termed internet addiction within professional circles. Indeed, this phenomenon can affect people regardless of gender, age, or educational background. However, scientific literature also identifies specific target groups that are more prone to internet addiction. We tend to believe that in certain cases, specific professions also create conditions that can shape corresponding tendencies in individuals to varying degrees. Therefore, such research is important and timely for identifying potential targets and developing appropriate strategies aimed at mitigating risks. The aim of the research conducted within the article is to investigate the potential for internet addiction based on an individual's profession, by identifying those at higher risk. The research is grounded in the works of Klimov and Holland on professional classification, Orzack's views on the characteristics of internet addiction, and Young's methodology, which helps determine the level of internet dependency. Based on our research, we find that individuals whose professional activities are directly related to the use of internet resources are in the most at-risk zone for internet addiction. This is because, outside of work, people use the opportunities provided by the Internet to meet various needs, thereby becoming targets for potential addiction.
Keywords: Internet addiction; profession; information society; excessive use of the Internet; self-management skills